Critical Discourse Analysis of Teun A. Van Dijk's Model against Online News “The Decline in Refinery Profits Threatens to Increase Oil Prices” - Aida Zavirah Fayruza; Hanik Mahliatussikah; Mahmoud Khalif Khudair Al Hayani (Arabic Education Department, Islamic Studies Faculty, Universitas Muhammadiyah Malang, 2021)
This study aimed to describe the dimensions of the text of the Teun A Van Dijk' model in the text discourse online news “the decline in refinery profits threatens to increase oil prices”. The rise of online media news coverage regarding the decline in refinery profits threatening the increasing oil prices interests the researchers in analyzing the discourse because the author considers that no mass media is completely neutral and objective. This research used a qualitative descriptive method with Teun A Van Dijk’s theoretical framework of critical discourse analysis, because the Van Dijk’s model also looks at the social cognition of the unit of observation and the social context in which the unit of observation occurs. The result of the research revealed that most of the dimensions of the text structure were met. Social analysis that is obtained was the decrease in refinery profits will cause new problems in public social life. For the textual analysis of macrostructure elements, the topic described a common theme of this online news which is